Community perception of biodiversity conservation within protected areas in Benin - VODOUHE, Gbèlidji Fifanou; COULIBALY, Ousmane; ADEGBIDI, ANSELME BIENVENU E. ADÉNIYI; SINSIN, Brice (My University, 2010)
Commitment of local communities to protected areas is essential for conserving biodiversity. However, in many developing countries like Benin, former management strategies kept human from protected areas using coercion. Fortunately, more recent regimes attempt to give local populations more control on the management but little is known about local residents' perceptions, beliefs and attitudes toward the management of these areas. This study, carried out around the Pendjari National Park, determined factors which support local communities' positive perceptions towards biodiversity conservation in the park, analysed their assessment of current park management activities compared to former management approaches and draw the implications for effective participatory management of protected areas. We collected socio-demographic data from 164 residents on their awareness of conservation methods. We used Stepwise Discriminant Analysis to differentiate the variables that had the greatest power for discriminating between local residents' perception to conserve or not biodiversity and tomanage the park. The findings indicated that the positive behavior of local communities towards conservation of biodiversity within Pendjari National Park was highly correlated with the current management strategy that involved more effectively local communities, the educational level of participants and their geographical origins. Participants' perceptions of biodiversity conservation were strongly related to locally perceived benefits. Although 89% of participants were favorable to the concept of biodiversity conservation within the park, the decision to ban encroachments due to agricultural activities increased negative opinion on this park management option. Our results suggested that understanding local residents' perceptions and using them as a starting point to improve the park–people relationship could help park management staff to involve more effectively local communities and improve their awareness about biodiversity conservation within the park.
Keywords: Benin; biodiversity conservation; Pendjari National Park; local communities; people perception; resource use